The court and the Constitution - Cox, Archibald, 1912-2004. (Boston : Houghton Mifflin, 1987)
Building a nation, from laissezfaire to the welfare state, constitutional adjudication as an instrument of reform
PART I. Building a Nation -- Miracle at Philadelphia -- Judicial Supremacy -- Federal Power and Supremacy -- Opening a National Market -- One Nation Indivisible -- PART II. From Laissez-Faire to the Welfare State -- Economic Liberty -- Dual Federalism -- Judicial Self-Restraint Under the New Deal -- The Expansion of Federal Power -- PART III. Constitutional Adjudicationas an Instrument of Reform -- The Warren Court -- The Nonconformists -- National Security and the First Amendment -- Protection for the Accused -- School Desegregation -- Affirmative Action -- Political Equality -- Invidious Distinctions and Fundamental Rights -- Abortion -- PART IV. Constitutionalism and the Rule of Law -- The Future of Judicial Review
Includes bibliographical references (pages 381-403) and index
Keywords: United States. -- Supreme Court -- History; United States. -- Supreme Court -- History; États-Unis. -- Supreme Court -- Histoire; Constitutional history -- United States; Judicial review -- United States -- History